A companion to early modern Rome, 1492-1692
1 online resource.
Keywords: This volume, edited by Pamela M. Jones, Barbara Wisch, and Simon Ditchfield, focuses on Rome from 1492-1692, an era of striking renewal: demographic, architectural, intellectual, and artistic. Rome's most distinctive aspects--including its twin governments (civic and papal), unique role as the seat of global Catholicism, disproportionately male population, and status as artistic capital of Europe--are examined from numerous perspectives. This book of 30 chapters, intended for scholars and students across the academy, fills a noteworthy gap in the literature. It is the only multidisciplinary study of 16th- and 17th-century Rome that synthesizes and critiques past and recent scholarship while offering innovative analyses of a wide range of topics and identifying new avenues for research. Contributors are: Renata Ago, Elisa Andretta, Katherine Aron-Beller, Lisa Beaven, Eleonora Canepari, Christopher Carlsmith, Patrizia Cavazzini, Elizabeth S. Cohen, Thomas V. Cohen, Jeffrey Collins, Simon Ditchfield, Anna Esposito, Federica Favino, Daniele V. Filippi, Irene Fosi, Kenneth Gouwens, Giuseppe Antonio Guazzelli, John M. Hunt, Pamela M. Jones, Carla Keyvanian, Margaret A. Kuntz, Stephanie C. Leone, Evelyn Lincoln, Jessica Maier, Laurie Nussdorfer, Toby Osborne, Miles Pattenden, Denis Ribouillault, Katherine W. Rinne, Minou Schraven, John Beldon Scott, Barbara Wisch, Arnold A. Witte.